Delayed Sigmoid Ischemic Rupture Following Open Repair Abdominal Aortic Aneurysm. (August 2017) - Kotsis, Thomas; Christoforou, Panagitsa; Asaloumidis, Nikolaos; Papaconstantinou, Ioannis
Colon ischemia following aortic reconstruction is a severe complication with an incidence of 1% to 2% of the operated patients; this infrequent complication will be lethal for nearly half of these patients. Commonly, colon ischemia may be an intraoperative observation or an early postoperative finding. However, in the case presented here, sigmoid rupture and small and large intestine communication was revealed 3 months following repair of the abdominal aorta. A 71-year-old man, following open repair of an abdominal aortic aneurysm, went home on the fifth postoperative day. Four months later, he was admitted to the emergency department of our hospital, because of fever, diarrhea, and abdominal pain for about 5 days. After conservative treatment and improvement in symptoms, the patient was released only to return to hospital with the same symptoms after a month. On this second admission, the symptoms were initially mild and the patient seemed to improve, but suddenly he deteriorated and an exploratory laparotomy was conducted, which revealed a left colon ischemia and a communication between the sigmoid and the small intestine. A left hemicolectomy was performed, along with a temporary colostomy (Hartmann diversion). The patient, 2 years after the initial aortic repair and 10 months following the complete restoration of the large intestine continuity, is well with no further manifestations.